The Integration Of Arab-Malay Philological Studies And Modern Rhetorical Theory In Strengthening Nusantara Cultural Identity - Yuyun Sri Wahyuni; Fenty Sukmawaty; Nadira Permata Sandi (UNIVERSITAS PAKUAN, 2026)
This study aims to examine the integration of Arab-Malay philological studies and modern rhetorical theory in explaining the role of Malay-Islamic manuscripts as a medium for constructing the cultural identity of the Nusantara. Previous philological studies have primarily focused on textual criticism, transliteration, and manuscript reconstruction, while the rhetorical dimensions embedded in Arab-Malay manuscripts have received relatively limited scholarly attention. This research employs a qualitative approach through library research, combining philological analysis and rhetorical criticism. The primary sources consist of influential Arab-Malay manuscripts within the Malay-Islamic intellectual tradition, including Hikayat Amir Hamzah, Hikayat Nabi Bercukur, Syair Perahu, Taj al-Salatin, and Bustan al-Salatin. The analysis is conducted by identifying Aristotelian rhetorical elements—ethos, pathos, and logos—and interpreting cultural meanings through the perspectives of cultural hybridity and social habitus. The findings reveal that Arab-Malay manuscripts function not only as historical documents and literary heritage but also as rhetorical instruments that establish moral authority, reinforce Islamic values, and reproduce Malay-Islamic cultural identity. The interaction between Arab-Islamic traditions and local Malay culture has generated a distinctive form of cultural hybridity that enriches the character of Nusantara civilization. Furthermore, the rhetorical strategies embedded in these manuscripts contribute significantly to the formation of collective consciousness and social habitus within Malay society. This study proposes an interdisciplinary analytical framework that broadens the scope of philological inquiry and highlights the continuing relevance of Arab-Malay manuscripts in strengthening the cultural identity of the Nusantara amid contemporary globalization and cultural transformation.